DIGITAL MARKETING AND PRODUCT LITERACY ON GENERATION Z' INTEREST IN USING SHARIA BANKS: PEMASARAN DIGITAL DAN LITERASI PRODUK TERHADAP MINAT GENERASI Z DALAM MENGGUNAKAN BANK SYARIAH - Riyan Pradesyah (LPPM UPMI, 2023)
This research aims to see the influence of digital marketing and product literacy on generation Z's interest in using Sharia Banking. The development of sharia financial institutions is certainly familiar to the public, it's just that the market share of sharia banks is still experiencing insignificant development. For this reason, this research uses two independent variables, namely digital marketing and product literacy, to measure generation Z's interest in using sharia banks. This research is quantitative research using SmartPLS as data processing. The results obtained show that there is an influence of digital marketing (X1) on generation Z's interest in using sharia banks (Y) of 5,979, and there is an influence of Product Literacy (X1) on generation Z's interest in using sharia banks (Y) of 4,671, and this can confirmed by the model ???? 1 = 5,979 ???? 1 + 4,671 ???? 2 + ???? .